Development of novel nanomaterials for fingerprinting - Syahirunnisa Binte Mahadi (2017)
Fingerprint analysis has been used in forensic science for more than 100 years, as it aids in criminal identification. Visual fingerprint recognition has often been used, to visually match the prints to the suspect. Recently, surface assisted laser desorption ionisation time-of-flight mass spectrometry (SALDI-ToF-MS) is another chemical analysis method that has been developed to analyse fingerprints. In SALDI-ToF-MS, inorganic compounds have been used as a matrix component to transfer the energy from the laser to the analyte, causing the analytes to ionise and identified through a mass spectrometry. Novel nanomaterials, namely hydrophobic and hydrophilic iron oxide nanoparticles coated with silica doped carbon black (silica/CB), were developed in recent years as a matrix compound for both of these purposes. However, there is room for improvement in the development of these nanomaterials. In this project, the main aim is to improve the silica/CB thickness on the iron oxide nanoparticles, to improve signal intensities obtain from SALDI-ToF-MS. These were made through modifications to the synthesis process of the silica/CB coating. First, the effect of changing the surface agent to ammonium hydroxide was investigated. Subsequently, the reagent ratio was varied to optimise the synthesis process. An alternating step was also attempted to build the coating sequentially on the nanoparticles. These synthesised powders were then characterised to understand the changes made due to the synthesis process. The functionality and usability of the powders were also tested by dusting of fingerprints and SALDI-ToF-MS. Effectively, the change in surface agent and alternating step performed well, even with the limitations considered form the testing methods. These modifications could potentially be included in the synthesis protocols, to produce powders effective for fingerprint analysis.